1991
DOI: 10.1021/jo00008a054
|View full text |Cite
|
Sign up to set email alerts
|

Revised structure of bryostatin 3 and isolation of the bryostatin 3 26-ketone from Bugula neritina

Abstract: Bryostatin 3 and the corresponding 26-ketone 5, which represents a new bryostatin, were isolated from the marine bryozoan Bugula neritina (Bugulidae). Spectmecopic data from 2D NMR studies indicate that the structure of bryostatin 3 (3) has to be revised to structure 4. Bryostatin 3 showed [sH]phorbol dibutyrate receptor displacement activity similar to that of bryostatin 1, whereas the corresponding 26-ketone 5 was significantly less active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…[203][204][205][206][207][208][209][210][211][212][213][214][215][216] Several of the initially published structures were later revised (bryostatins 3, 4, 5 and 10), 211,217 which still leads to some confusion in the literature. In addition, mass spectrometric evidence exists that bryostatins are also present in other, unrelated marine organisms.…”
Section: Bryostatinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[203][204][205][206][207][208][209][210][211][212][213][214][215][216] Several of the initially published structures were later revised (bryostatins 3, 4, 5 and 10), 211,217 which still leads to some confusion in the literature. In addition, mass spectrometric evidence exists that bryostatins are also present in other, unrelated marine organisms.…”
Section: Bryostatinsmentioning
confidence: 99%
“…330 Gr€ afe et al found that 199 passively conveys protons and other monovalent cations through membranes, which could explain the antibacterial and cytotoxic effects. 331 In addition to 199 and 207, several further congeners were described (200)(201)(202)(203)(204)(205)(206)(208)(209)(210)(211)(212)(213)(214)(215)(216)(217). [332][333][334][335][336][337][338] Noteworthy is the occurrence of the structurally related clathrynamides 212-217 in the marine sponges Clathria sp.…”
Section: Macrolactinsmentioning
confidence: 99%
“…The bryostatin antitumor macrolides [1] continue to capture the imagination and attention of chemists and life scientists alike, not only for their novel biological properties, but also for the significant challenges and opportunities they provide for doing high-level organic synthesis. In this Focus Review, we highlight some of the more significant developments that have taken place in the bryostatin total synthesis field over the period [2001][2002][2003][2004][2005][2006][2007][2008][2009], since work prior to 2001 has already been reviewed by us, [2] as well as in several even earlier review articles by Wills, [3] Wender, [4] Pettit, [5] and Paterson.…”
Section: Introduction and Historymentioning
confidence: 99%
“…In this Focus Review, we highlight some of the more significant developments that have taken place in the bryostatin total synthesis field over the period [2001][2002][2003][2004][2005][2006][2007][2008][2009], since work prior to 2001 has already been reviewed by us, [2] as well as in several even earlier review articles by Wills, [3] Wender, [4] Pettit, [5] and Paterson. [6] Originally discovered in extracts of the marine organism Bugula neritina by George Pettit and co-workers in the late 1960s, [1] the bryostatin antitumor macrolides have now expanded to become a family of some twenty members. [1] The first bryostatin to succumb to structure elucidation was bryostatin 1, back in 1982.…”
Section: Introduction and Historymentioning
confidence: 99%
See 1 more Smart Citation